Etomidate is devoid of genotoxicty and mutagenicity in human lymphocytes and in the Salmonella typhimurium/microsomal activation test. (October 2020) - Cavalcanti, Bruno Coêlho; do Amaral Valente Sá, Lívia Gurgel; de Andrade Neto, João Batista; de Sousa Silva, Antônio Adailson; Rios, Maria Erivanda França; Barreto, Francisco Stefânio; de Oliveira Ferreira, José Roberto; da Silva, Cecília Rocha; Barroso, Fátima Daiana; Magalhães, Hemerson Iury Ferreira; Nobre, Hélio Vitoriano; de Moraes, Manoel Odorico
Abstract: No carcinogenesis or mutagenesis studies have been carried out with etomidate. The current study showed that etomidate has weak cytotoxic potential after 48 h exposure in human lymphocytes and has no hemolytic activity. The weak cytotoxicity seems to be related with redox imbalance of etomidate (40.9 and 81.9 μM) treated lymphocytes. At both etomidate concentrations, a slight decrease of the levels of GSH intracellular content and a significant increase in the amount of carbonylated proteins were observed after 48 h. The contribution of oxidative stress to genetic toxicity was only perceived when the enzyme Fpg was applied in the comet assay. Etomidate (40.9 and 81.9 μM) is a weak generator of oxidative DNA damage in lymphocytes. These damages to DNA probably were repaired, since no DNA strand breaks were detected in the standard alkaline comet assay (in the presence or absence of hepatic S9 microsomal fraction) without Fpg. Also, no micronucleated lymphocytes or carrying chromosomal aberrations were observed. Finally, etomidate (2046.8 and 4093.5 μM) was not mutagenic in the Salmonella /microsome mutagenicity assay, which used four Salmonella typhimurium strains (TA97a, TA98, TA100, and TA102) to detect frameshift and base-substitution mutations. In summary, etomidate is a weak oxidative DNA damaging anesthetic and is devoid of mutagenic properties in eukaryotic and prokaryotic models. Highlights: Etomidate induces a weak cytotoxic effect on PBLs after 24 h and 48 h. A small amount of DNA strand breaks levels were detected in the modified comet assay (employment of FPG enzyme). The oxidative DNA lesions were almost completely repaired which reflects in the lack of mutagenesis. No increases in revertants numbers on S. typhimurium /microsome test.